Design and Development of an Android-Based Application for Receiving and Tracking Menu Orders in a Café - Rama; Mustamin Tewa; Muhammad Iswal Burhan (Journal of Electrical Engineering and Informatics, 2026)
This research aims to design and create  an Android-based order menu receiving and tracking application for Kopitawa X Empal Gepuk Cafe in Makassar to improve efficiency and accuracy in order management. Application development is carried out using  a waterfall approach  which consists of five main stages, namely, needs analysis, design, implementation, verification, and maintenance. The technology used includes the Dart programming language with the Flutter framework and Firebase as the database management system. Testing based on the ISO/IEC 25010 standard shows the application has a good level of feasibility. Functional suitability reaches 100%, indicating that all key features are functioning as needed. Optimal performance efficiency with 19% CPU usage and 81 MB of memory. Usability scored 77.9% in the "Good" category, while portability ensures that the app runs smoothly on various android devices including versions 10 to 14. This application can provide practical benefits by making it easier for café staff to manage orders, speed up the service process, and monitor sales performance. In addition, the application can also serve as a reference in the development of similar systems in the café and other restaurant business sectors, with the potential to continue to be developed through feature updates and improved data security.